How did a lower drink‐drive limit affect bar trade and drinking practices? A qualitative study of how alcohol retailers experienced a change in policy. (8th December 2019) - Sumpter, Colin; Mohan, Andrea; McKell, Jennifer; Lewsey, James; Emslie, Carol; Fitzgerald, Niamh
Abstract: Introduction and Aims: Reducing the legal drink‐drive limit from 0.08% to 0.05% blood alcohol concentration (BAC) can reduce road traffic accidents and deaths if properly enforced. Reduced limits may be opposed by alcohol retail and manufacturing industries on the basis of commercial impact. Our aim was to qualitatively explore how a reduction in the drink‐drive limit from 0.08% to 0.05% BAC in Scotland, was experienced by bar owners or managers, including any resultant changes in customer drinking or business practice. This is the first study of this type. Design and Methods: Semi‐structured interviews were conducted with 16 owners and managers of on‐trade premises in Scotland in 2018, approximately three years after the drink‐drive limit was reduced. Data were analysed using thematic analysis. Results: Most participants reported no long‐term financial impact on their business, but a few, mainly from rural areas, reported some reduction in alcohol sales. Observed drinking changes included fewer people drinking after work or leaving premises earlier on weekdays. Adaptations to businesses included improving the range of no/low‐alcohol drinks and food offered. Changes such as these were seen as key to minimising economic impact. Discussion and Conclusions: Opposition to legislative measures that impact on commercial interests is often strong and receives significant public attention. This study found that Scottish businesses that adapted to the drink‐drive limit change reported little long‐term economic impact. These findings are of international relevance as potential BAC limit reductions in several other jurisdictions remain the subject of debate, including regarding the impact on business.